Efficient syntheses of 3-hydroxyimino-1-isoindolinones and 3-methylene-1-isoindolinones via Cu-promoted C–H activation–nitroalkylation–intramolecular cyclization tandem processes. Issue 33 (10th April 2017) - Yu, Lin; Huang, Hang; Chen, Xiang; Hu, Liang; Yu, Yongqi; Tan, Ze
Abstract : Efficient and selective syntheses of 3-hydroxyimino-1-isoindolinones and 3-methylene-1-isoindolinones were achieved via 8-aminoquinoline assisted Cu-promoted coupling of benzamides with nitroalkanes. Abstract : Efficient and selective syntheses of 3-hydroxyimino-1-isoindolinones and 3-methylene-1-isoindolinones were achieved via 8-aminoquinoline assisted Cu-promoted coupling of benzamides with nitroalkanes. The reaction was found to go through C–H activation, nitroalkylation followed by intramolecular cyclization. 3-Hydroxyimino-1-isoindolinones were obtained with nitromethane whereas 3-methylene-1-isoindolinones were produced with higher nitroalkanes.